Differences in the Triplechem Learning Model with Balinese Local Wisdom and the Discovery Learning Model in Influencing Students' Visual Literacy and Mental Models about Acid-Base Solutions - I. W. Suja; I. M. G. Jayadiningrat; I. N. S. Ardiyasa (Jurnal Pendidikan IPA Indonesia, 2023)
This study intends to investigate the differences in the effect of the TripleChem learning model with Balinese local wisdom and the Discovery Learning model on students' visual literacy and chemical mental models about acid-base solutions. The research was designed using a quantitative approach and classified as quasi-experimental. The research design used was a pretest-posttest non-equivalent control group design. The population of this study was 206 junior high school students with Balinese cultural backgrounds with various beliefs (religions), namely Hindus, Muslims, and Christians. Cultural content will cause learning to be more contextual, more interesting, and bring students closer to their own culture. The sampling was done using a simple random sampling technique, and obtained two sample classes, one class as the experimental group, and the other as the control group. The experimental group was taught using the TripleChem learning model containing Balinese local wisdom, while the control group was taught using the Discovery Learning model. The dependent variable in this research was visual literacy and students' mental models of chemistry. Data collection was carried out using a visual literacy test (10 items in total; item validity between 0.520 – 0.893; and test reliability coefficient of 0.895) and a chemical mental model test (8 items in total; item validity between 0.669 – 0.878; and test reliability coefficient of 0.922). Data analysis was carried out descriptively and MANCOVA. The results show that the TripleChem learning model is more effective to be applied to improve students' visual literacy and mental models about acid-base solutions compared to the Discovery Learning model. This condition is caused by the syntax of the TripleChem learning model which is more sequential and structured to build students' visual literacy and chemistry mental models. The application of the TripleChem learning model in chemistry learning needs to be supported by laboratory facilities to display chemical macroscopic phenomena and animated media to explain these phenomena at the level of matter particles.